Assessment terhadap Pemerlu Pelayanan Kesejahteraan Sosial (PPKS) di Yayasan Smilingkids Foundation - Adek Ayu Wandira; Fajar Utama Ritonga; Emi Triani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This Field Work Practice (PKL) was conducted at SmilingKids Foundation Medan, focusing on assisting a child with leukemia who had temporarily dropped out of school due to long-term medical treatment and the family's economic limitations. The practice aimed to apply the individual social work method (case work) to improve the client’s social functioning through the stages of assessment, planning, intervention, monitoring, evaluation, and termination. The methods used included observation, interviews, and documentation studies to identify the client’s social, psychological, and economic conditions, as well as the available support systems. The assessment results indicated that the client’s health condition and financial difficulties had negatively affected access to education, learning motivation, and social interaction. The intervention, consisting of a homeschooling program combined with psychosocial support, successfully improved the client’s basic academic skills, self-confidence, and enthusiasm for learning. The monitoring and evaluation process showed that the program had a positive impact on the child’s academic and psychosocial development. Therefore, it can be concluded that the case work approach through a homeschooling program is an effective social intervention in helping children with cancer maintain their right to education while enhancing their overall social functioning.